Moderating effect of age group on interrelationship between knowledge, future time perspective and retirement planning preparation among Sarawak government employees, Malaysia - Abang Ibrahim, Dayang Kartini (2021)
This study was designed to extend the planning model of retirement by including holistic perspective into existence with the direct relationship of knowledge and Future Time Perspective and indirect relationship of moderation effect of Age Group among employees in government sectors in Sarawak. The studies on retirement mostly were developed from a representative sample of Americans over age 50 conducted by Survey research center (SCR) at the Institute for Social Research (ISR) at the University of Michigan and supported by the National Institute of Ageing (NIA) since the beginning of the mid 1980’s to address contemporary retirement issues of the labor force. However, studies on the retirement issues regarding health, social context, families, all of which can affect the decision and preparation to retire need to be investigated, not only looking at financial issue as per se. In this regard, a conceptual model was developed as a foundation for the research framework, a model of retirement planning and preparation has been adapted all along with established theories related to retirement. The developmental aspect of the model is designed to convey the view that for individuals, a tendency of understanding the challenge (cognitive development) on understanding retirement before making any decision is crucial and significant. This behavior will lead to positive attitude towards planning and preparation and would be expected to be maintained overtime. Holistic approach in the study explained how people could shape the directions of their own lives, by looking at retirement as a whole rather than only looking at financial matters. In order to meet the objectives of the study a cross- sectional, correlational survey design was used, and standard self –administered questionnaires were used to gather data among 283 employees in different government sector which are situated at the same location. Descriptive analysis and Structural Equation modeling (SEM) were conducted for data analysis. The descriptive findings of the study revealed that there is no significant difference between knowledge and Age Group among employees [F(2,280)=l.4l6, p= 0.244]; p <.05 significant level. Similarly in second objective, there is no significant difference also between employees’ future time perspective with Age Group [F(1,281)=.036, p= 0.849]; p < .05 significant level. On the other hand, in third objective of the study, there was a significant difference between retirement planning and preparation and age group among employees [F(l,28l)= 3.737, p= 0.05]; p <.05 significant level. The result of Structural Equation Model analysis indicated that there is no significant relationship between knowledge and retirement planning and preparation of the employees whereby result from the SEM did not provide the statistical support for a significant effect between the construct with standardized beta estimate value of -0.306 at p= 0.793 (p<0.05). On the other hand, the result has unveiled that there is a significant relationship between future time perspective and Retirement Planning and Preparation with the standardized beta estimate value of 0.238 at p= 0.021 (p<0.05). Finally, the results revealed that age group moderated the relationship between knowledge and retirement planning and preparation. As for relationship between future time perspective and retirement planning and preparation, there were no statistical results to support the assumption. Thus, the moderation effect is not supported. As for awareness and readiness to plan and prepare for retirement, the result indicates that the highest (M=11.07, SD=2.806) indication that the awareness and readiness of individual in RPP is in Retirement Preparedness, as for the second highest was Retirement Goal (M=19.43, SD=3.576), compared to Retirement Decision (M= 24.49, SD= 3.679) and Retirement Representation (M=12.71, SD=4.020).The results indicated that the retirement representation among individual are at present but when it comes to action of planning and preparing, it was to no avail. This study provided a unique contribution to research by developing a framework for future research by combining empirically grounded findings together with theoretical explanation from the literature. This study has shown that different culture, different perspective and lack of awareness and readiness among individuals in retirement planning and preparation does affect the result of this study and its assumption. Since most of the empirical evidence were from the developed countries and many research has been done on western individuals, this study has shown that there is a need to do in depth research and studies on retirement planning and preparation since the result of this current study has made significant different between empirical studies in developed and developing countries. This study also highlighted some implication and recommendations for policy and practice toward the improvement of employees in their retirement planning and preparation.